Reviews in computational chemistry. - Lipkowitz, Kenny B.; Boyd, Donald B. (Reviews in Computational Chemistry., 1998)
VOLUME 12: REVIEWS IN COMPUTATIONAL CHEMISTRY. Kenny B. Lipkowitz and Donald B. Boyd. HOW DOES ONE COMPUTE FREE ENERGY AND ENTROPY FROM MOLECULAR SIMULATIONS? WHAT HAPPENS WHEN SIMULATIONS ARE RUN WITH CONSTRAINTS? HOW SHOULD SIMULATIONS BE PERFORMED TO MODEL INTERFACIAL PHENOMENA? HOW IS DENSITY FUNCTIONAL THEORY USED TO SIMULATE MATERIALS? WHAT QUANTUM MECHANICAL METHODS SHOULD BE USED TO COMPUTE NONLINEAR OPTICAL PROPERTIES OF MATERIALS? WHICH PARAMETERS ARE MOST INFLUENTIAL IN A MOLECULAR SIMULATION? HOW CAN CRYSTAL STRUCTURES BE PREDICTED? TUTORIALS PROVIDING ANSWERS TO THESE QUESTIONS AR.